2015
DOI: 10.1007/s13580-015-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Air anions improve growth and mineral content of kale in plant factories

Abstract: Air anions affect plant growth by stimulating various biological mechanisms. We investigated the effect of atmospheric anion concentrations on plant growth and mineral concentration in kale (Brassica oleracea var. acephala cv. TBC) plants cultivated in a plant factory. Kale seedlings grown under normal growth conditions for two weeks were transplanted to a nutrient film technique (NFT) system in a plant factory equipped with light-emitting diodes (LEDs) [red:white:blue (RWB) = 8:1:1 and red:green:blue (RGB) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…There are many references to report the possible biological effects [ 24 , 32 , 33 , 35 , 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. And some of them were listed in Table S2 .…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many references to report the possible biological effects [ 24 , 32 , 33 , 35 , 38 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. And some of them were listed in Table S2 .…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%
“…NAI treatment improved sprout growth and bacterial control during plant development [ 112 ]. NAIs have a positive effect on kale growth by improving fresh weight, macroelements and microelements [ 113 ]. However, no significant difference was observed between control and NAI-treated tobacco plants in nicotine and total alkaloid; the total nitrogen content in NAI-treated plants was slightly increased when compared with control plants [ 114 ].…”
Section: Biological Effects Of Negative Air Ions On Human/animal Hmentioning
confidence: 99%
“…Mineral content Mineral content of microgreens and mature lettuce was determined following a slightly modified wet digestion method as suggested by Havlin and Soltanpour (1980) [18]. In short, following the method described by [19], exactly 0.1 g of dried shoot was analyzed with an ICP-OES spectrophotometer (PlasmaQuant 9100 ICP-OES Analytik jena. Jena, Germany) for P, K, Ca, Mg, S, Fe, Mn, Zn, and Cu.…”
Section: Methodsmentioning
confidence: 99%
“…According to Kotaka et al, the action of ions (positive or negative) in the air can affect variations in plant respiration [3]. Song et al [4] and Lee et al [5] showed the impact of air anions on the growth of lettuce and kale, respectively. Seed germination starts with water uptake by the seed and ends with embryonic axis extension.…”
Section: Introductionmentioning
confidence: 99%